Institutional Ownership, Audit Quality, Gender Diversity and Political Connection to Tax Aggressiveness in Indonesia - Fachrul Ananto Firdaus; Siti Nurlaela; Endang Masitoh (Politeknik Negeri Madiun, 2021)
This study aims to empirically prove the influence of Institutional Ownership, Audit Quality, Gender Diversity, and Political Connection to Tax Aggressiveness. This study used a sample of companies listed on the LQ 45 Indonesia Stock Exchange during the period 2013 – 2019. The sample usage in this study was 13 LQ 45 companies with purposive sampling og 91 sampels during 2-13 – 2019 listed on the Indonesia Stock Exchange. The research method used in this study was the panel data regression model. The results showed that the quality of audits had a positive effect and political connections negatively influenced tax aggressiveness while institutional ownership an gender diversity had no effect on tax aggressiveness.